Autologous Fat Grafting With Combined Three-Dimensional and Mirror-Image Analyses for Progressive Hemifacial Atrophy. Issue 3 (September 2016) - Yang, Xiaonan; Wu, Rongwei; Bi, Hui; Lu, Haibin; Jia, Zhenhua; Jin, Xiaolei; Qi, Zuoliang
Abstract : Background: Autologous fat grafting (AFG) has been widely used to treat progressive hemifacial atrophy (PHA). However, objective and quantitative analyses in patients with PHA are complicated because of multidimensional atrophy and fat absorption. This study aimed to introduce a new method to predict volumetric deficiency of soft tissues and objectively evaluate the survival of grafted fat with 3-dimensional (3D) and mirror-image analysis (MIA). Methods: Thirty-one patients with PHA were classified into 2 groups based on the location of the facial midsagittal plane (FMP), which was established through our proposed method using nasion (point a), anterior nasal spine (point b), and pogonion (point c). The included cases with centered FMP were treated using serial AFG and followed up for 12 to 15 months. Images were obtained preoperatively (pre-OP) and postoperatively at 2 time points (3 months and 12 months). Three-dimensional computed tomography (CT) was performed before the first surgery to locate the FMP and predict the volumetric deficiency of soft tissues with MIA. Three months after the first surgery, 3D laser scanning was conducted to evaluate the volume of surviving fat. Patient characteristics, satisfaction, and soft tissue augmentation results were analyzed. Results: Twenty-seven cases (9 men and 18 women) with PHA were included and treated using serial AFG (mean number of operation, 3.1 times). The mean age was 22.1 years. With 3D CT or 3D laser-scanning camera and MIA, we obtained the mean deficient volume of the affected area (30.48 mm 3 ) and the mean volume of the total fat injection (133.61 mm 3 ). The mean fat absorption ratio was 47.92%. The mean satisfaction score immediately obtained at first postoperative (score = 4.3) was higher than that at 3 months postoperatively (score = 4.1) and 12 months postoperatively (score = 4.0). No complications and donor-site morbidity were noted. Conclusion: The facial symmetry of patients with centered FMP can be successfully restored using serial AFG alone. The combined 3D and MIA can be used to predict the volumetric deficiency of soft tissues and objectively evaluate the survival of grafted fat.